Tribological investigation of graphene as lubricant additive in vegetable oil - Kiu, S.S.K. (Penerbit Universiti Sains Malaysia, 2017)
In this study, the tribological behaviours of graphene nanoparticles as lubricant additive in vegetable oil were investigated as a function of nanoparticle concentration. Graphene nanoparticles were added at 25 ppm, 50 ppm and 100 ppm as additive into vegetable oil as lubricant through hydrodynamic and acoustic cavitation as homogenising mechanism. The tribological properties of each homogenised solution were tested using a four-ball machine according to ASTM D4172. Wear scar diameter and friction coefficient were the determining parameters in this study. The results showed that 50 ppm is the optimum concentration that recorded the lowest wear scar diameter and friction coefficient as compared to control sample. © Penerbit Universiti Sains Malaysia, 2017.